New models of sustainable mobility in Smart Cities - Vincenzo Auriemma; Luisa Nardi (Academicus International Scientific Journal, 2025)

(untitled)
The aim of this study is to explore new models of sustainable mobility in smart cities, with a particular focus on the intersection between digitalisation, social inclusion and sustainable urban planning. Through an interdisciplinary analysis combining bibliographic review and international case studies (Barcelona, Singapore, Milan, Amsterdam, Oslo and Tokyo), the work highlights how urban mobility is now at the heart of a technological and cultural transformation. The adoption of advanced digital systems, such as artificial intelligence and Mobility-as-a-Service, not only improves efficiency and reduces environmental impact, but also contributes to redefining social relations and urban governance models. However, critical issues related to digital inequalities, trust in institutions and civic participation are emerging. The paper proposes a multidimensional approach based on the triple bottom line theory, which integrates environmental sustainability, social equity and economic development. Therefore, inclusive and participatory policies become fundamental to ensuring that sustainable mobility becomes a common good capable of promoting more resilient, accessible and fair cities.